A FOURTH-ORDER FINITE DIFFERENCE SOLVER FOR POISSON'S EQUATION VIA THE HALF-SWEEP ARITHMETIC MEAN (HSAM) METHOD - J. Sulaiman et al. (Proceedings of ICMSA, 2005)
The main purpose ofthis paper is to validate the efficiency and accuracyof the Half-Sweep Arithmetic Mean (HSAM) method using the fourth orderfinite difference approximation equation to solve one-dimensionalPoisson's equation. In this paper, we formulate the Full-Sweep andHalf-Sweep Arithmetic Mean methods, namely FSAM and HSAMrespectively. Finally some computational experiments were conductedto prove that the fourth-order solver using the HSAM methods issuperior to the FSAM method.Keywords: Half-Sweep Iterative, Arithmetic Mean Algorithm, Fourth-Order Finite Difference, Poisson's equation